Development of Student Activity Sheets (SAS) Based on Project Based Learning to Improve Creative Thinking Skills on Electrolyte and Nonelectrolyte Solution Material - Prasasti, Tiara Dwi; Mitarlis, Mitarlis (Asian Journal of Science Education, 2025)
This study aims to produce Student Activity Sheets (SAS) based on project based learning to improve creative thinking skills on electrolyte and nonelectrolyte solutions material that are feasible to use as learning media. The research method employed in this study was the 4-D model (Define, Design, Develop, and Disseminate), but it was limited to the Develop stage. A limited trial was conducted with 35 students from one of the senior high schools in Surabaya. Regarding validity, the SAS was found to be valid, showing content and construct validity with a mode of 4 each in the good category. Regarding practicality, the SAS was confirmed to be very practical, with the result of students responses indicating a percentage of 95.89% the very good category, supported by student activities with a mode of 5 in the very good category and an implementation learning percentage of 95.56% in the very good category. Regarding effectiveness, SAS was deemed to be effective as indicated by the improved students creative thinking skills and learning outcomes through pretest and posttest results, where 60% of students achieved an N-gain in the high category and 40% achieved an N-gain in the medium category. The N-gain results for each indicator of creative thinking skills were as follows: fluency at 0.67, flexibility at 0.77, originality at 0.53, and elaboration at 0.74. Based on their validity, practicality, and effectiveness, SAS based on project based learning to improve creative thinking skills on electrolyte and nonelectrolyte solution material is feasible to use as a learning media.